Моделювання фізичних процесів під час розробки комп'ютерних ігор - Коваленко, О. М.; Мазурова, М. М. (ХНУРЕ, 2025)
Modeling physical processes in game development is important for improving the gaming experience and making it more immersive for players. By using principles from different areas of physics, such as motion, forces, and light, developers can create more realistic interactions and environments. Simulating physical effects like fluid dynamics and material properties also helps in producing accurate visual effects, which increases the overall realism of the game. Game engines play a major role in bringing these physical processes into the game, making both the graphics and mechanics feel more believable.
Keywords: розробка комп'ютерних ігор; комп'ютерна гра